Personalized home-care support for the elderly: a field experience with a social robot at home - Di Napoli, Claudia; Ercolano, Giovanni; Rossi, Silvia (User modeling and user-adapted interaction, 2023)
Socially assistive robotics (SAR) is getting a lot of attention for its potential in assisting elderly users. However, for robotic assistive applications to be effective, they need to satisfy the particular needs of each user and be well perceived. For this purpose, a personalization based on user’s characteristics such as personality and cognitive profile, and their dynamic changes is a crucial factor. Moreover, most of the existing solutions rely on the availability of specific technological infrastructures, generally requiring high economic investment, and that cannot be easily placed in different environments. Personalization and adaptation of assistive robotics applications to different user’s characteristics and needs, and even to different technological environments, are still not fully addressed in real environments. In the present work, the results of the UPA4SAR project are presented. The project aimed at providing a social robotic system to deliver assistive tasks for home care of patients with mild cognitive impairment in a personalized and adaptive way. We introduce the general architecture of the system and the developed robotic behaviors. Personalization and dynamic adaptation of assistive tasks are realized using a service-oriented approach by taking into account both user’s characteristics and environmental dynamic conditions. Field experimentation of the project was carried out with 7 patients, using the robotic system autonomously running in their homes for a total of 118 days. Results showed a reliable functioning of the proposed robotic system, a generally positive reaction, and a good acceptability rate from patients.